A dança na escola: uma proposta pedagógica para a disciplina de componente eletivo nonovo ensino médio - Dantas, Viviane dos Santos (2020)
This artistic / educational dissertation is entitled “Dance at Scholl: A Pedagogical Proposal for the Discipline of Elective Component in New High School.” Its generalobjective is to describe pedagogical itineraries in Dance, developed in my teaching at the Centro Estadual de Educação ProfissinalDr. Ruy Pereira dos Santos, a public professional education high school. To apply this research, it was necessary to: (1) know the current conjuncture of Art / Dance Teaching in the curriculum; (2) and develop this teaching through the Klauss Vianna Technique at school. Based on the Klauss Vianna Technique (TKV) carried out in the Elective Component Discipline “Knowing Yourselfthrough a New Look”(Conhecendo-se por um novo olhar –in Brazilian Portuguese), which enables the subject to be integrally based on Somatic Education. In this context, we seek to expand the discussion in the face of the new conjuncture of high school today in Brazil. And for this discussion, the following questionsare brought: How could Dance and Technique Klauss Vianna be inserted in the integral formation of this student in High School? What are the possible contributions of dance education to the integral education of this student at this level of education? In this text, we also consider Somatic Education as dance content at school, as an element of contribution to the integral formation of this subject. To answer the mentionedquestions, we used the descriptive qualitative methodology, under the bias of bibliographic and observation methods,in which we addressed some points about the teaching of Art in the light of the Brazilian Common National Curricular Base (BNCC, 2018) and Law 13.415 / 2017. Isabel Marques (2001) is thetheoretical reference in the field of dance education at school and as a methodological basis the understanding of the body proposed by Klauss Vianna (2005), and for the systematization and application of the Klauss Vianna Technique to teacher Jussara Miller (2007 ). The research proposes a dialogue about my experience as a teacher at Centro Estadual de Educação ProfissionalDr. Ruy Pereira dos Santos, sited in São Gonçalo do Amarante -Rio Grande do Norte (RN), with interfaces in the Klauss Vianna Technique (TKV ). To carry out this research, the dance classes were distributed in the Discipline of Elective Component, which is inserted in the Axis of Technical and Professional Training of the Curriculum in the School in Full Time, which is based on the Model of the School of Choice, created in the year of 2000, in Recife -PE, at Gymnasium Pernambucano by a former student from that place, who went throughthe abandonment of that institution